A role of expression level of reference and investigated genes in prostate tumors for qPCR analysis - Gerashchenko, G.V.; Stakhovsky, E.O.; Chashchina, L.I.; Gryzodub, O.P.; Kashuba, V.I. (Вiopolymers and Cell, 2018)
Aim. To determine the expression profiles of a set of cancer-associated genes in prostate tumors, using various normalization protocols (with 1, 2 and 4 reference genes) and to optimize a combination of reference genes to calculate the relative expression (RE) of the investigated genes in prostate cancers. Methods. Relative expression level of 23 genes was analyzed by quantitative PCR (qPCR) in 37 prostate cancer tissues (T) with different Gleason scores (GL) and at various stages and compared with 37 corresponding normal prostate tissue (CNT) samples and with 20 samples of prostate adenomas. Results. Theoretical calculations of the RE deviation showed no influence of the normalization protocols on the results for both the reference and the investigated genes. The experimental data that were calculated using a 2–ΔΔCt showed statistically significant differences in the expression of 17 out of 23 investigated genes, when the paired T/CNT were compared. RE values calculated using the 2–ΔCt method showed a high similarity of statistical data in all reference gene groups for tumor-CNT-adenoma groups (> 82 %). Data grouping by a cancer stage showed 69 %, and by the GL score – 64.5 % of the data overlapping. Conclusions. All three types of normalization protocols, as expected, can be used for RE normalization in prostate tumor samples. The usage of either the 2–ΔCt or 2–ΔΔCt models showed no difference in the calculated RE levels for the studied reference genes. The most important factor was the constitutive expression of the reference genes. Moreover, the expression levels of the investigated genes, changes in RE values, number of samples in groups and heterogeneity of gene expression are important parameters for the selection of the threshold in expression level differences between groups for a reliable data interpretation. Мета. Визначити профілі експресії пухлино-асоційованих генів у пухлинах передміхуровоїзалози з використанням різних протоколів нормалізації (з одно-, дво- тачотириреференсними генами АБО з одним, двома та чотирма референсними генами) таоптимізувати комбінації референсних генів для розрахунку відносної експресії (ВЕ) у ракупередміхурової залози. Методи. Кількісною ПЛР (кПЛР) проаналізовано ВЕ 23 генів у 37 зразках тканин передміхурової залози (Т) з різними показниками Глісона та різнимистадіями пухлин у порівнянні з 37 умовно-нормальними зразками тканини передміхуровоїзалози (УНТ) та 20 зразками аденом передміхурової залози. Результати. Теоретичнірозрахунки відхилення ВЕ не підтвердили впливу значень рівнів експресії на цей параметрані у ВЕ референсного гена, ані у ВЕ досліджуваних генів. Експермиментальні дані, якібули отримані, з використанням 2–ΔΔCt моделі, показали статистичні значущі відмінності у експресії 17 з 23 досліджуваних генів, при порівнянні парних T/УНТ. Показники ВЕ, розраховані з використанням моделі2–ΔCt, показали високий рівень співпадіннястатистичних даних у всіх групах референтних генів для груп аденокарциноми-УНТ-аденоми (понад 82 %). Слід зазначити, у 69% випадків, а за показниками Глісона – у 64,5 %. Висновки. Всі три типи референсних генів, як і було передбачено, можуть бутивикористані для нормалізації ВЕ у зразках пухлини передміхурової залози. Використаннямоделей 2–ΔCt або 2–ΔΔCt не має впливу на рівень ВЕ для референсних генів. Найважливішимфактором була їх стабільна експресія. Важливими параметрами для вибору порогувідмінностей рівнів експресії між групами з метою правильної інтерпретації даних є рівніекспресії досліджуваних генів, величина зміни значень ВЕ, розмір вибірки та високагетерогенність експресії. Цель. Определить профили экспрессии ряда опухоль-ассоциированных генов в опухолях предстательной железы, используя различные протоколы нормализации (одним, двумя и четырьмя референсными генами) и оптимизировать комбинацию этих генов для рассчета относительной экспрессии (ОЭ) исследуемых генов при раке предстательной железы. Методы. Количественной ПЦР (кПЦР) було проанализировано ОЭ 23 генов в 37 образцах рака предстательной железы (Т) с различными показателем Глисона и на разных стадиях, в сравнении с 37 условно-нормальными образцами ткани простаты (УНТ) и 20 образцами аденом предстательной железы. Результаты. Теоретические расчеты отклонения ОЭ не подтвердили влияния величины уровней экспрессии на этот параметр ни в ОЭ референсного гена, ни в ОЭ исследуемых генов. Экспериментальные данные, полученые с использованием 2–ΔΔCt модели, показали статистически значимые различия экспрессии у 17 из 23 исследованных генов при сравнении парных Т/УНТ. ОЭ, рассчитанные с использованием модели 2–ΔCt, показали высокий уровень совпадений статистических данных во всех группах референсных генов для групп аденокарциномы-УНТ-аденомы (более 82 %). Следует отметить, что при разделении по стадиям совпадение статистических данных наблюдалось в 69 % случаев, а по показателю Глисона – в 64,5 %. Выводы. Все три типа референсных генов, как и ожидалось, могут быть использованы для нормализации ОЭ в образцах опухолей простаты. Использование моделей 2–ΔCt или 2–ΔΔСt не показало влияния различий в уровнях ОЭ для референсных генов. Наиболее важным фактором была их стабильная экспрессия. При выборе порога уровней экспрессии между группами с целью правильной интерпретации данных важными параметрами являются уровни экспрессии исследуемых генов, величина изменения значений ОЭ, размер выборки и высокая гетерогенность экспрессии.